2013
DOI: 10.2337/db12-1139
|View full text |Cite|
|
Sign up to set email alerts
|

Flavonoid Apigenin Is an Inhibitor of the NAD+ase CD38

Abstract: Metabolic syndrome is a growing health problem worldwide. It is therefore imperative to develop new strategies to treat this pathology. In the past years, the manipulation of NAD+ metabolism has emerged as a plausible strategy to ameliorate metabolic syndrome. In particular, an increase in cellular NAD+ levels has beneficial effects, likely because of the activation of sirtuins. Previously, we reported that CD38 is the primary NAD+ase in mammals. Moreover, CD38 knockout mice have higher NAD+ levels and are pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
171
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(179 citation statements)
references
References 43 publications
(89 reference statements)
7
171
1
Order By: Relevance
“…With Lineweaver-Burk analysis, we found that CD38 noncompetitively inhibits CD38 with decreasing V max and unchanging K m with increasing inhibitor concentration. This is in contrast with prior studies that identified luteolinidin as a competitive inhibitor of CD38 (Kellenberger et al, 2011;Escande et al, 2013). Consistent with noncompetitive inhibition, the decreasing V max cannot be overcome by increasing substrate concentration, unlike with competitive inhibition (Michaelis et al, 2011).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…With Lineweaver-Burk analysis, we found that CD38 noncompetitively inhibits CD38 with decreasing V max and unchanging K m with increasing inhibitor concentration. This is in contrast with prior studies that identified luteolinidin as a competitive inhibitor of CD38 (Kellenberger et al, 2011;Escande et al, 2013). Consistent with noncompetitive inhibition, the decreasing V max cannot be overcome by increasing substrate concentration, unlike with competitive inhibition (Michaelis et al, 2011).…”
Section: Discussioncontrasting
confidence: 55%
“…Flavonoid anthocyanidin compounds were recently shown to inhibit CD38 with relatively high potency compared with previously used inhibitors, with luteolinidin found to be the most potent of the flavonoids tested (Kellenberger et al, 2011;Escande et al, 2013). Anthocyanidins, such as luteolinidin, are a subgroup of the broad family of flavonoids, which has thousands of known compounds (Nijveldt et al, 2001) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings provide mechanistic evidence that apigenin downregulates CD38 expression in type II diabetic rats. This data is consistent with the apigenin-mediated improvement of glucose homeostasis via SIRT1 activation and promotion of fatty acid oxidation along with reduction of lipids accumulation (Escanade et al, 2013). Importantly, our study reveals that pharmacological downregulation or inhibition of CD38 expression at the molecular level can be a therapeutic approach to treat T2D.…”
Section: Discussionsupporting
confidence: 75%
“…CD38 enzyme is a NAD + ase which degrades NAD + in tissue and promotes metabolic syndrome (Escanade et al, 2013). Our findings provide mechanistic evidence that apigenin downregulates CD38 expression in type II diabetic rats.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation